Latin America since independence two centuries of continuity and change - Wright, Thomas C. (Latin American silhouettes: studies in history and culture, 2017)
This innovative text offers a clear and concise introduction to Latin America since independence. Thomas C. Wright traces continuity and change in five central colonial legacies: authoritarian governance; a rigid social hierarchy based on race, color, and gender; the powerful Roman Catholic Church; economic dependency; and the large landed estate. The text's user-friendly illustrations, maps, chapter summaries, and suggestions for further reading enrich student understanding of a major part of the world.